Agro- Industrial Integration from an Accounting Perspective Study in General Company for Leather Industries/Baghdad (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
The General Company for Leather Industries is an economic production unit that contributes to supporting the national economy in the field of manufacturing natural leather and exploiting it by producing clothes, shoes and bags based on the principle of economic account and efficiency of investing public funds and its effectiveness in achieving the objectives of the state and raising the performance levels of the national economy in order to achieve the goals of development plans, so the goal of the research is to identify the obstacles facing the General Company for Leather Industries / Baghdad (research sample) which transforms Without agricultural industrial integration with its animal branch and orientation towards imported leather to achieve its objectives despite the existence of tanning factories in the same company through a cost comparison of the product in case of dependence on local leather and application of agricultural industrial integration on the one hand and in case if the skins imported by another and four models of men's shoes (7566,7639, 6730,7545) contained in the company's records in October 2014, and one of the most important findings of the research is that there are many obstacles to agricultural industrial integration that need real solutions from the state and that its application does not achieve The company's objectives of